Edukasi bahaya plastik terhadap kesehatan dan lingkungan - Ummah, Hanik Arifatul (Maliki Interdisciplinary Journal, 2024)
Nowadays, the majority of people prefer to wear and use tools made of plastic. According to them, plastic material is very simple, light, and not easily broken. Most of them do not know the impact caused by the excessive use of plastic materials. When talking about where the main ingredients for making plastic come from, In general, plastics are composed of macromolecules formed through polymerization processes. Plastic production also comes from natural gas and crude oil. The use of plastic is widely used in everyday life; we can take examples from the medical sector, lectures, and offices. Not only that, but plastic materials also generate a lot of waste. While the waste generated from plastic materials is difficult to decompose in nature and requires a long period of time, From a medical point of view, the use of plastic materials is not recommended for long-term use. It will also have a dangerous impact, especially on health.